Difference of Dietary Habit on Type 2 Diabetes Mellitus Patients at Perumnas I Public Health Center, West Pontianak - Silaban, Agatha; Putri, Eka Ardiani; Tejoyuwono, Agustina Arundina Triharja (JUXTA: Jurnal Ilmiah Mahasiswa Kedokteran Universitas Airlangga, 2024)
Highlights: Good eating habits can control the blood sugar levels and BMI of type 2 DM patients. Good dietary control includes the schedule, amount, and type of food consumed. The schedule recommendation for type 2 DM consists of six meals a day, divided into three large meals and three times breaks.   Abstract Introduction: In 2019, type 2 diabetes mellitus (DM) at Perumnas I Public Health Center was sixth-placed among the top ten diseases with 1,118 cases. This study aimed to determine the dietary habits of type 2 DM patients based on body mass index (BMI) and fasting blood glucose at Perumnas I Public Health Center, West Pontianak. Methods: This was an observational analysis study with a cross-sectional design. A total of 78 type 2 DM patients who were treated from January to July 2021 at Perumnas I Public Health Center were involved in this study. This study used a three-day food record questionnaire to get patients' food dishes and the Wilcoxon test for correlation between variables. Results: Most of the respondents had a calorie deficit for three days straight (70.5% on the first day, 76.9% on the second day, and 71.8% on the third day), a normal BMI (51.3%), and above-normal fasting blood glucose (88.5%). The p-value of the Wilcoxon test that showed dietary habits on the first day, the second day, and the third day with BMI was 0.000. The p-value of the Wilcoxon test that showed dietary habits on the first day, the second day, and the third day with fasting blood glucose was 0.000. This showed a significant distinction between patients' three-day dietary habits and their BMI and fasting blood glucose. Conclusion: There was a significant difference between nutritional status and fasting blood glucose in three-day dietary habits in type 2 DM patients at Perumnas I Public Health Center, West Pontianak.